Sistem Pendukung Keputusan Penentuan Lokasi Usaha Kuliner Menggunakan Metode Analytic Hierarchy Process (AHP) dan Technique for Others Reference by Similarity to Idealsolution (TOPSIS) - Isyriyah, Laila; Maulidi, Rakhmad; Fandi, Achmad Zaza Sandri A (Jurnal Teknologi dan Manajemen Informatika, 2024)
This study focuses on developing a Decision Support System (DSS) to assist culinary business owners in selecting optimal business locations. The research integrates the Analytic Hierarchy Process (AHP) and the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) methods into the decision support system. AHP is used to objectively determine the weights of several criteria through pairwise comparisons, while TOPSIS is employed to evaluate location alternatives based on their proximity to the ideal solution. The AHP and TOPSIS calculations reveal that criterion K3 (Distance from transportation facilities) has the highest weight of 0.3053, followed by K1 (Distance from residential areas) with a weight of 0.2698, highlighting that accessibility to residential areas and public transportation are important factors in business location selection. Integrating the DSS with a Map API further aids users in making location-related business decisions.